A mutation in C. neoformans mitochondrial NADH dehydrogenase results in increased virulence in mice - Mitch Merryman (Taylor & Francis Group, 2020)
Cryptococcus neoformans: (H99W) was serially passaged in the invertebrate wax moth Galleria mellonella fifteen times to study how fungal virulence evolves under selection and whether those adaptations affect virulence. The G. mellonella passaged strain (P15) and the pre-passage H99W strains were used to infect three different host models of C. neoformans: C. elegans, G. mellonella, and Balb/c mice. While there was no difference in survival in the invertebrate models, P15 killed mice faster than H99W through both intratracheal and intravenous routes of infection and mice infected intravenously with P15 showed higher fungal burden in the brain. Characterization of the major virulence factors of C. neoformans found that P15 had increased capsule size, GXM release, and melanization. Whole genome sequencing of P15 and H99W revealed two mutations in P15, an insertion in the promoter region of NADH dehydrogenase (CNAG_09000) and an insertion in the LMP1 gene (CNAG_06765). Both ATP production and metabolic rate were higher in P15 compared to H99W. Quantitative RT-PCR suggested that the increased ATP was due to increased RNA levels of NADH dehydrogenase. Thus, adaptation to growth in hemocytes resulted in increased production of ATP, increased metabolic rate, and increased virulence in mice. This was likely due to differential expression of virulence factors, which skewed the host immune response to a less efficient Th2 response, with higher levels of IL-4, IL-10, and TNF-α in the brain. Overall, serial passage experiments have increased our understanding of how this yeast evolves under innate immune selection pressure.